Clinical Anatomy of the Lower Extremity Veins-Topography, Embryology, Anatomical Variability, and Undergraduate Educational Challenges - Marian Simka; Joanna Czaja; Agata Kawalec (MDPI AG, 2024)
Veins of the lower extremity can be categorized into three hierarchically ordered groups: the epifascial, the interfascial, and the deep ones. In the past, the interfascial veins, e.g., the great saphenous vein, were categorized as superficial veins. But nowadays, experts recommend regarding these veins as a separate group because of their unique topography and clinical relevance. In order to better understand the venous anatomy of the lower limbs, which is highly variable, one should also comprehend their embryological development. Venous embryogenesis in the lower limb consists of three stages. During the first stage the primitive fibular vein is the main vein of the extremity. During the second stage it is replaced by the axial vein and finally by the femoral vein. In some adult individuals this embryonic or fetal venous anatomy is still present. Unfortunately, current anatomical textbooks and atlases, as well as traditional cadaver dissections, are not very useful regarding these issues. Therefore, undergraduate teaching of anatomy can be challenging. New educational tools, such as ultrasonography, seem indispensable to teach the anatomy of these veins properly.